Whiteness in the novels of Charles W. Chesnutt - Wilson, Matthew, 1949- (University Press of Mississippi, 2004)
Charles W. Chesnutt (1858-1932), critically acclaimed for his novels, short stories, and essays, was one of the most ambitious and influential African American writers of the late nineteenth and early twentieth centuries. Today recognized as a major innovator of American fiction, Chesnutt is an important contributor to de-romanticizing trends in post-Civil War Southern literature, and a singular voice among turn-of-the-century realists who wrote about race in American life. Whiteness in the Novels of Charles W. Chesnutt is the first study to focus exclusively on Chesnutt's novels. Examining th.